The concept of intellectual safety in educational institutions between contextualization and consistency - Al-Shihri, Hassan bin Faiz (Arab Journal for Sciences and Research Publishing, 2016)
The present study aimed to identify the various philosophies of intellectual security and identify the intellectual influences that contribute to the formation of the concept of intellectual security and to highlight the role assigned to educational institutions in enhancing the concept of intellectual security. The descriptive analysis approach was used to achieve the goals of the study.The study is based on the analysis of the qualitative content of the concepts carried out on the subject of the study, whether directly or indirectly, to analyze and study it. The results of the study noted a kind of confusion and ambiguity which in turn led to difficulty in finding the mechanism that works to promote this concept, In the educational institutions, and that there is a kind of clear contrast in the concept of intellectual security between Islam and the West in the light of different philosophies, and represents the concept of intellectual security Islamic model of the ideal application, by keeping pace with developments and events steadily, which earned him a kind of flexibility, Aspects of life, various economic, political, social, cultural and others. And that the concepts of intellectual security - in a number of times - are different in priorities and contentions among the global communities according to their political, social, religious and cultural orientations. What is considered in Muslim society is the security of thought, in other systems it is a secondary matter that has no consideration.